Diseño e implementación de un sistema automático para reducir el tiempo de enfriamiento en la línea de producción del chocolate en la micro-empresa de los hermanos monje ubicados en el cantón Pujili en el periodo 2014-2015 - Chancusig Casa, Alex Geovanny (2015)
The implementation of this automatic continuous cooling of chocolate, it took place at Cotopaxi Province in Pujilí Canton; in the micro-enterprise of the Hnos. Monje. This company is dedicated to the elaboration of artisan chocolate which now owns machinery for perfon the preparation of this product. But lacking of autonomous systems that allow perform the same processes in less time, for this reason the owner provided the necessary support for its development of designing and implementation of a cooling tunnel. Based on the inverted cycle of Carnot; for being the most used in construction of domestic refrigeration systems and industrial refrigeration....